2022
DOI: 10.48550/arxiv.2206.03331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving the Diagnosis of Psychiatric Disorders with Self-Supervised Graph State Space Models

Abstract: Single subject prediction of brain disorders from neuroimaging data has gained increasing attention in recent years. Yet, for some heterogeneous disorders such as major depression disorder (MDD) and autism spectrum disorder (ASD), the performance of prediction models on large-scale multi-site datasets remains poor. We present a two-stage framework to improve the diagnosis of heterogeneous psychiatric disorders from resting-state functional magnetic resonance imaging (rs-fMRI). First, we propose a self-supervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…For example, graph explainability techniques [Ying et al, 2019, Huang et al, 2022 could be utilized to find potential functional connectivity biomarkers for phenotypes and psychiatric disorders. The application of graph self-supervised learning techniques Fedorov et al [2021], , Peng et al [2022] and graph normative modelling [Gazzar et al, 2022] on non-clinical datasets would assist in learning representations that could further be transferred to a downstream clinical tasks. Graph augmentation methods Zhao et al [2021] could boost the statistical power of the clinical datasets and assist in solving the problem of labeled data scarcity and regularize overfitting.…”
Section: Discussionmentioning
confidence: 99%
“…For example, graph explainability techniques [Ying et al, 2019, Huang et al, 2022 could be utilized to find potential functional connectivity biomarkers for phenotypes and psychiatric disorders. The application of graph self-supervised learning techniques Fedorov et al [2021], , Peng et al [2022] and graph normative modelling [Gazzar et al, 2022] on non-clinical datasets would assist in learning representations that could further be transferred to a downstream clinical tasks. Graph augmentation methods Zhao et al [2021] could boost the statistical power of the clinical datasets and assist in solving the problem of labeled data scarcity and regularize overfitting.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we compare the results yielded by our method with SOTA methods that also use fMRI data from the REST-MDD dataset. Several studies (Gallo et al, 2021;Yan et al, 2019) achieved accuracy ranging from 61% to 63% in MDD versus HC classification on REST-MDD, and a latest research (Gazzar et al, 2022) obtained an accuracy of 63%. It can be observed that the results of these SOTA studies are not that promising, suggesting that there is a great challenge in performing the fMRI-based MDD detection task on REST-MDD.…”
Section: Comparison With Exiting Studiesmentioning
confidence: 99%